Gender-Specific Flood Vulnerability in Sirajganj Sadar Upazila: An Index-Based Analysis of Multi-Dimensional Impacts - Rifat Bin Hossain; Md. Minhaz Uddin; Sanjida Saif Neha; Rifah Tasfia (The Innovation of Social Studies Journal, 2025)
The interplay between gender and vulnerability is crucial in understanding the impact of climate change-induced flooding. Men and women employ distinct adaptive strategies in response to these events, with significant differences observed between male-headed households (MHHs) and female-headed households (FHHs). This study analyzed the social, infrastructural, economic, and environmental dimensions of vulnerability using a mixed-methods approach, including surveys, interviews, and focus group discussions with 216 households. Findings from the weighted average index (WAI) revealed that FHHs experience higher vulnerability across all dimensions, particularly in social and physical aspects. The disparity in multidimensional vulnerability between MHHs and FHHs is statistically significant, as shown by a t-test (F = 3.423, p-value = 0.000). Specifically, 42% of FHHs fall into the very high vulnerability category, compared to just 6% of MHHs. The study identifies sociocultural norms as key contributors to this disparity, influencing households' ability to respond to and recover from flood-related disasters. To mitigate future impacts, the study recommends targeted interventions for FHHs, including improved access to services, capacity-building initiatives, awareness training, livelihood support programs, and greater involvement in disaster preparedness and risk reduction strategies. Addressing these factors is essential for enhancing resilience and reducing vulnerability among FHHs in the face of climate change.